Buffer-aided multiple-antenna relay strategy for 5G systems - Jun ZHAN; Qifa YAN; Xiaohu TANG (Dianxin kexue)
Buffer-aided multiple-antenna relay technology can provide the 5G communication system with wide coverage,and improve the system throughput performance effectively.A three-node multiple-antenna buffer-aided relay system was investigated and thus an optimal buffer-aided relay strategy,namely joint adaptive link selection and power allocation protocol,which maximizes the average throughput of system was proposed.The analytical results indicate that the optimal link selection policy depends only on the current instantaneous channel state information and the statistical channel information of related links,and the optimal power allocation scheme has equal power allocation for the transmitted data flows.The simulation results show that buffer used in relay could significantly improve the throughput of relay system compared to the relay system without buffer.In addition,the MIMO technique can achieve the multiplexing gain by multiple antennas,and then improve the throughput of buffer-aided relay system further.